The diagnostic value of soluble urokinase plasminogen activator receptor (suPAR) compared to C-reactive protein (CRP) and procalcitonin (PCT) in children with systemic inflammatory response syndrome (SIRS) - KEPENEKLİ KADAYİFCİ, EDA; HAKLAR, GONCAGÜL; ALTINKANAT GELMEZ, GÜLŞEN; CİNEL, İSMAİL HAKKI; ÖZTÜRK, MAKBULE NİLÜFER; ŞİRİKÇİ, ÖNDER; DEMİRCİOĞLU, SERAP (ELSEVIER SCIENCE BV, 2017)
Background: The aim of the present study was to determine the diagnostic and prognostic values of suPAR and to compare them to CRP and PCT in pediatric patients with systemic inflammatory response syndrome (SIRS). Material-methods: A prospective case-control study was performed. The study was performed in a tertiary university hospital which has a 649-bed capacity. Patients included 27 children with SIRS and 27 control subjects without any infection or immunosuppressive condition. Blood samples were obtained on the day of admission and on the 4-7th days of the hospital stay. Results: The median (minemax) serum levels of suPAR obtained on the first day of the admission were 10.06 (2.7-57.46) and 2.22 (1.08-5.13) ng/Ml for the SIRS group and control group, respectively. The median serum levels of suPAR in the SIRS group was significantly higher than that in the control group (p < 0.05). The serum suPAR levels was significantly higher in nonsurvivors than in survivors in SIRS group (p < 0.05). In the SIRS group, the area under the receiver operating characteristics curve (AUC(ROC)) for suPAR revealed an optimum cut-off value, sensitivity, specificity, NPV and PPV of 0.978, 3.8 ng/mL, 96%, 96%, 96%, and 96%, respectively. Conclusions: We conclude that suPAR does have diagnostic value in children with SIRS. Additionally, persistent high serum suPAR level predicts mortality in SIRS in children. (C) 2016 Japanese Society of Chemotherapy and The Japanese Association for Infectious Diseases. Published by Elsevier Ltd. All rights reserved.
Keywords: Soluble urokinase plasminogen activator receptor; SIRS; Children; PREDICTS MORTALITY; LEVEL